Confinement-induced infrared absorption by H2 and N2 gases in a porous silica aerogel. (October 2016) - Vander Auwera, J.; Boulet, C.; Carré, Y.; Kocon, L.; Hartmann, J.-M.
Abstract: Transmission spectra in the fundamental bands of H2 and N2 gas inside the pores of a silica aerogel sample were recorded at room temperature and for several pressures using a Fourier transform spectrometer. They first show that, as the absorption is proportional to the pressure, it is due to the interactions of the molecules with the inner surfaces of the pores and not to the dipole induced during gas-phase molecule–molecule collisions. Furthermore, the analysis of the widths and areas of the observed absorption structures indicate that, for the considered aerogel sample, most of the absorption is likely due to "free" molecules moving within the pores with a weak contribution of adsorbed molecules. Graphical abstract: Highlights: Infrared absorption by confined gases. Porosimetry using CO absorption lines. H2 and N2 spectra inside a porous aerogel. "Free" versus adsorbed species contributions.